The Relationship between Study Habits and Academic Achievement in English Education Study Program at Baturaja University - Yentri Anggeraini; Episiasi, Episiasi; Salsabilla Putri Nandaini (Universitas Lancang Kuning, 2024)
The problem of this research was “is there correlation between study habits and academic achievement in English education study program at Baturaja University”?. Therefore, this study aims to describe whether or not it is there correlation between students’ habits and academic achievement of the students. This study used correlational design. The population of the research was 67 students. The questionnaire and documentation were used for collecting the data. To analyze the data , researchers used Pearson – Product Moment Correlation and descriptive statistics using the SPSS ver.25. The result showed that there is no or weak correlation between study habits and academic achievement in English Education Study Program at Baturaja University (r = 0.062, p>0.05). In conclusion, some factors that influence learning achievement were not only study habits, but also students’ learning motivation, their learning environment, facilities by educational institutions and it can affect their academic achievement.